2012
DOI: 10.5402/2012/970629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Physical Activity Program on Markers of Endothelial Dysfunction, Oxidative Stress, and Metabolic Status in Adolescents with Metabolic Syndrome

Abstract: The metabolic syndrome (MetS) is a precursor of diabetes. Physical activity (PA) improves endothelial dysfunction and may benefit patients with MetS. Aims. To evaluate the effect of a physical activity (PA) program on markers of endothelial dysfunction and oxidative stress in adolescents with (MetS). Methods. We carried out a cohort study of 38 adolescents with and without MetS (18 females and 20 males). All participants completed a 3-month PA program. All variables of the MetS as well as markers of endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
0
15
0
3
Order By: Relevance
“…In patients with CAD, greater weight reduction following exercise training was associated with a greater increase in FMD, suggesting a dose response effect [87]. Physical activity also improved plasma markers of endothelial function and oxidative stress in adolescents with the metabolic syndrome [90]. In type 2 diabetic patients, weight loss and increased physical activity have been shown to improve endothelial function [91][92][93].…”
Section: Lifestyle Interventionsmentioning
confidence: 89%
“…In patients with CAD, greater weight reduction following exercise training was associated with a greater increase in FMD, suggesting a dose response effect [87]. Physical activity also improved plasma markers of endothelial function and oxidative stress in adolescents with the metabolic syndrome [90]. In type 2 diabetic patients, weight loss and increased physical activity have been shown to improve endothelial function [91][92][93].…”
Section: Lifestyle Interventionsmentioning
confidence: 89%
“…Esta situación es preocupante ya que el sedentarismo es uno de los comportamientos de riesgo que presenta mayor prevalencia en la actualidad. La práctica de actividad física regular está relacionada con la disminución de los riesgos de enfermedades cardiovasculares y los beneficios son mayores si se inicia en etapas tempranas de la vida (30)(31)(32)(33).…”
Section: Universidadunclassified
“…Numerous studies have shown the strong relationship between the risk of death from cardiovascular diseases and obesity [1][2][3]. This phenomenon is not only limited to adults, but it also applies to obese children and adolescents [3].…”
Section: Introductionmentioning
confidence: 97%
“…Nowadays, approximately 16% of children worldwide are obese, and the prevalence of obesity in children and adolescents is associated with endothelial dysfunction, cardiovascular diseases, and mortality [1,3]. Researchers also point out that obese children older than 10 years are more susceptible to dyslipidemia, high arterial blood pressure, metabolic disorders and cardiovascular diseases [2]. One of the most common cardiovascular diseases is atherosclerosis, which is the accumulation of lipids and fatty substances in the blood vessels leading to vasoconstriction and decreased blood flow to the muscle myocardial occlusion of the vessel wall [4].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation